Test Effectiveness of Ethanol Extract Ointment Papaya Leaves (Carica Papaya L.) Against Healing of Cut Wounds on White Rabbit - Rahma, Ayu; Wahyuni, Dhea Sri; Susanti, Susanti (LPPM STIKes Muhammadiyah Ciamis, 2025)
Wound is a state of damage to body tissue caused by animal bites, scratchessharp objects. A rapid wound healing process is expected. Papaya leaf is effective as a wound healer, the use of extracts directly on the skin is not practical and optimal. In order to be practical and effective, it is formulated in the form of ointment preparations. This study aims to determine the effectiveness of papaya leaf (Carica papaya L.) ethanol extract ointment preparation in healing cut wounds in New Zealand white rabbits made in the form of ointment preparations. The extract was given with different concentrations of 5%, 10% and 15%. The ointment preparation was tested on test animals with a wound length of 2 cm. The positive control used was povidone iodine, while the negative control used ointment bases namely adeps lanae and vaseline album. The data were analyzed statistically using ANOVA (Analysis of Variant). Based on the results of the research that has been done, the concentration of papaya leaf ethanol extract ointment that is most effective in healing cuts is at a concentration of 15%.